STUDY ANALYSIS OF THE NUMBER OF VISITS OF REGIONAL LIBRARY FACILITIES IN THE CITY OF BANDUNG - Masyithah, Mutiara; Akbardin, Juang; Maknun, Johar (Journal of Development and Integrated Engineering, 2023)
The low interest in reading in the community is caused by inadequate library facilities, incomplete book collections and the difficulty of accessing libraries which are explained as the cause of the low interest in visiting librarians. . With this type of descriptive research approach, when writing this article, the author collects data and tries to describe the meaning and benefits of the results of the renovation activities in the library building itself. By choosing the building objects of the West Java Regional Library, the Bandung City Archives and Library Service and Pitimos, the author tries to describe the factors that decrease or increase the number of visits from the spatial form factor. And after that it can be concluded thatA library that facilitates its use is able to attract more visitors.